Development of Google Form Based on Scientific Literacy Principles for Junior High School Students in Heat Material. (February 2020) - MM, Renny Yunus; Irwandani; Asniati, Melisa; Anwar, Chairul; Subandi
Abstract: The research aims to develop and find out the attractiveness and feasibility of Google Form based on scientific literacy questions for junior high school students on heat material. This study uses the Borg and Gall model. The steps used in this research are potential and problems, inFormation gathering, product design, design validation, design revision, product testing, and product revision. The results showed that the percentage of media, material, and language experts were 94.7%, 89%, and 80%, the teacher's response was 90.41% and students' interest with a percentage of 87%. The trial instrument of 25 items was declared valid, reliable, and functioning well. So, it can be concluded that the instrument of Google Form based on scientific literacy questions for junior high school students on heat material meets the requirements of very decent quality and is very interesting to be used by students.